Respuesta :
Answer:
y=1
Step-by-step explanation:
5y(2x-1)=y(x+2)+20, x=3
5y(2(3)-1)=y(3+2)+20
5y(6-1)=y(5)+20
5y(5)=5y+20
25y=5y+20
25y-5y=20
20y=20
y=20/20
y=1
5y(2x-1)=y(x+2)+20, x=3
Step 1: Substitute x with 3
5y(2(3) - 1) = y(3 + 2) + 20
Step 2: Combine like terms in the parentheses
5y(6 - 1) = y(3 + 2) + 20
5y(5) = y(3 + 2) + 20
5y(5) = y(5) + 20
Step 2: Distribute the number outside the parentheses to the numbers inside the parentheses
25y = 5y + 20
Step 3: Combine like terms by subtracting 5y to both sides
25y-5y = (5y-5y) + 20
20y = 20
Step 4: Divide 20 to both sides to isolate y
[tex]\frac{20y}{20} = \frac{20}{20}[/tex]
y = 1
Check:
5(1) (2(3) - 1) = 1(3+2) + 20
5(6-1) = 1(5) + 20
5(5) = 5 + 20
25 = 25
Hope this helped!